SUBSTITUTION EFFECT OF FISHMEAL WITH EARTHWORM MEAL (Lumbricus sp) IN THE DIETS ON GROWTH OF CATFISH (Pangasius hypopthalmus) FINGERLINGS - Amaliah, Novi; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted for 56 days since 18th November 2015 to 16th January 2017. This study aims to determine the effect of substitution of fish meal with earthworm flour to the growth of the seed catfish. This experiment using a completely randomized design (CRD), which consists of 5 treatments and 3 replications, namely the replacement of fishmeal with flour earthworms respectively 0% (P1), 10% (P1), 20% (P2), 30% (P3), and 40% (P4) with the feed protein content of 30%. The fish samples used in this study are seed-sized catfish average weight of 2.0 grams with stocking density 20 birds per container experiment. Based on the results of this study concluded that earthworm flour can be used to substitute for fishmeal in feed seed catfish. The level of earthworm flour substitution is best with a substitution rate of 30% earthworm flour + 70% fishmeal.Key Word : Pangasius hypopthalmus, Earthworms, Substitution, Growth